The strategies for innovating with virtual reality and artificial intelligence: a literature review - Brzezinski, Mikołaj; Krzeminska, Izabella (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Metaverse, virtual reality, data science, and artificial intelligence are buzzwords that attract the attention of tech enthusiasts and corporate managers. The following article is a literature review that integrates the emerging domains of virtual reality/metaverse and artificial intelligence/data science into good use cases from a commercial perspective. As the result of the analysis, we propose four strategies that commercial organizations can use to harness the synergy of these domains for successful and effective Value Innovation management.